2019
DOI: 10.4269/ajtmh.19-0193
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hotspots in Schistosomiasis Consortium for Operational Research and Evaluation Studies for Gaining and Sustaining Control of Schistosomiasis after Four Years of Mass Drug Administration of Praziquantel

Abstract: Control of schistosomiasis presently relies largely on preventive chemotherapy with praziquantel through mass drug administration (MDA) programs. The Schistosomiasis Consortium for Operational Research and Evaluation has concluded five studies in four countries (Côte d'Ivoire, Kenya, Mozambique, and Tanzania) to evaluate alternative approaches to MDA. Studies involved four intervention years, with final evaluation in the fifth year. Mass drug administration given annually or twice over 4 years reduced average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 26 publications
4
64
0
1
Order By: Relevance
“…Villages were classified as "responders" if a decline exceeding the threshold was observed in both measures. 24 To supplement SCORE data on different treatment schedules and baseline infection prevalence and intensity, we derived data on a number of geographic and environmental features for each village, which are described in Table 2. All data-processing and subsequent statistical analysis were conducted in version 3.5.1 of the R software environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Villages were classified as "responders" if a decline exceeding the threshold was observed in both measures. 24 To supplement SCORE data on different treatment schedules and baseline infection prevalence and intensity, we derived data on a number of geographic and environmental features for each village, which are described in Table 2. All data-processing and subsequent statistical analysis were conducted in version 3.5.1 of the R software environment.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Kittur et al evaluated several definitions of PHSs in an analysis based on the first 3 years of SCORE data from Kenya and Tanzania and subsequently applied one of these definitions to describe the frequency and distribution of PHSs in the SCORE study. 11,24 Using this definition, we combined data from the SCORE studies with publicly available data related to geography, human population patterns, and climate to model characteristics that distinguish PHS villages from responders.…”
Section: Introductionmentioning
confidence: 99%
“…Despite treatment, there are hotspots where infection remains at persistently high levels 14,[134][135][136] . Hotspots can be caused by various programmatic factors such as poor treatment coverage/ adherence, movement of infected individuals and intense water contact.…”
Section: Evaluation Of Alternative Interventions and Strategiesmentioning
confidence: 99%
“…There are different de nitions of PHS. The approach adopted in the current study has been described elsewhere [13]. In brief, a village that failed to reduce the S. mansoni infection prevalence by at least 35% and/or failed to reduce the intensity of infection by at least 50% between baseline and year five testing is considered a PHS, while a village that ful ls these criteria is termed a low-prevalence setting.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, a village that failed to reduce the S. mansoni infection prevalence by at least 35% and/or failed to reduce the intensity of infection by at least 50% between baseline and year five testing is considered a PHS, while a village that ful ls these criteria is termed a low-prevalence setting. Of note, PHS of schistosomiasis have been investigated in different parts of the world [14][15][16][17] and in the gaining and sustaining control studies of SCORE [13]. Prior research showed that various factors can contribute to the existence of PHS, including close proximity of human habitation to open surface water bodies where intermediate host snails proliferate, human behaviours, particularly in terms of water, sanitation and hygiene (WASH) parameters [18][19][20] and socioeconomic status of the study population [21,22].…”
Section: Introductionmentioning
confidence: 99%